Students on the Move: The Future of International Students in the United States - Luu, Dao; Bain, Olga; Green, Madeleine (International Higher Education, 2007)
The American Council on Education released an issue brief, Students on the Move: The Future of International Students in the United States, in October 2006, that summarizes the existing research on international students in the Unites States and examines the US market position with respect to other major hosting countries in attracting international students. It found that while the United States continues to enroll the majority of international students, trends in other major hosting and sending countries suggests that US dominance cannot be taken for granted.